Perancangan Sistem Informasi pada Distributor Gas Elpiji dan Air Mineral UD. X di Sukoharjo - Kevin Farrel Kurniawan; I Gede Agus Widyadana; Iwan Halim Sahputra (Jurnal Titra, 2022)
UD. X is a distributor of LPG and mineral water located in the Sukoharjo area. Currently UD. X has not implemented information system technology in recording goods data, causing discrepancies in the actual inventory data. Inventory data discrepancies occur three to four times a week. To overcome these problems, it is necessary to have an information system that can make it easier to store data. The design of information systems begins with making ERD, context diagrams, and DFD. After that, it is continued by calculating the optimal order interval and calculating the minimum and maximum inventory needed by UD. X. Then proceed with making an information system application based on Microsoft Excel. The final result of the design of the information system is an application that has been designed to make it easier for admins to record accurately the inventory of goods and assist the owner in supervising the activities in and out of goods.